Promoting the health and wellbeing of children: A feasibility study of a digital tool among professionals - Skogberg Magda; Mackiewicz Karolina; Mänd Kristel; Tuuling Lehte; Urdzina-Merca Indra; Salanterä Sanna; Pakarinen Anni (Public Library of Science, 2022)
The foundations of children's health and wellbeing are laid in early childhood. A gamified app (EmpowerKids tool) was designed to support professionals to have discussions with 6- to 12-year-olds from low-income families about their health and wellbeing. The aim of this feasibility study was to evaluate the usability and acceptability of the tool from the perspective of professionals in social, health and education settings. The study was conducted using a one-group post-test-only design. The usability data were collected using System Usability Scale and the acceptability data were collected using an open-ended questionnaire distributed to professionals (n = 24) in Estonia, Finland and Latvia. The data were collected during two phases. The tool was modified further on the basis of the results. The total usability scores were 82/100 (first testing) and 84/100 (second testing), indicating excellent usability. The answers related to acceptability were divided into four categories: suitability for the context; satisfaction and quality; attractiveness; modification needs. The professionals perceived that the tool helped them to build an overall picture of a child's health and wellbeing, and to gain information about the child's individual needs. The requirements for modification detected during the first testing were mostly related to difficulties with textual expressions and graphics. No major modification requirements were expressed during the second testing. The tool is considered feasible and may be used by professionals from different settings to support children's health and wellbeing. Further studies are needed to evaluate the effectiveness of the tool from the perspective of child outcomes.